2012
DOI: 10.1111/j.1582-4934.2011.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

A fibronectin‐fibrinogen‐tropoelastin coating reduces smooth muscle cell growth but improves endothelial cell function

Abstract: Reendothelialization of the stent surface after percutaneous coronary intervention (PCI) is known to be an important determinant of clinical outcome. We compared the effects of biological stent coatings, fibronectin, fibrinogen and tropoelastin, on human umbilical vein endothelial cell (HUVEC) and vascular smooth muscle cell (VSMC) characteristics. Umbilical cord arterial segments were cultured on coated surfaces and VSMC outgrowth (indicating proliferation and migration) was measured after 12 days. mRNA was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…Recombinant human tropoelastin, displaying a wide range of biological activities, is especially suitable for mediation of the cell responses to biomaterials [2,4–5,2526]. Our results confirmed that the addition of tropoelastin constituents to silk-tropoelastin alloys promoted the attachment of HEFs and the endothelialization by HUVECs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Recombinant human tropoelastin, displaying a wide range of biological activities, is especially suitable for mediation of the cell responses to biomaterials [2,4–5,2526]. Our results confirmed that the addition of tropoelastin constituents to silk-tropoelastin alloys promoted the attachment of HEFs and the endothelialization by HUVECs.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, while cell proliferation was observed on all the three tropoelastin-containing samples, films contain higher ratio of tropoelastin tend to facilitate the formation of a better integrated endothelium (Figure 6C). This result confirmed that, in addition to enhanced cell attachment, the tropoelastin components in the protein alloys had a positive impact on accelerated HUVEC endothelialization [26]. …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This hemocompatibility has led to translational studies with tropoelastin coatings on metallic vascular stents which present tropoelastin's cell attachment functionality, allowing for enhanced endothelialization, decreased smooth muscle cell proliferation and stent hemocompatibility [3,11,12]. These effects are seen both in vitro and following implantation, where in vivo studies confirm that tropoelastin coatings preferentially enhance endothelialization, while suppressing underlying smooth muscle cell infiltration and hyperproliferation [13]. With the accelerating use of tropoelastin materials for vascular applications, it is increasingly important to broaden the understanding of tropoelastin cell signaling mechanisms.…”
mentioning
confidence: 76%
“…have found that tropoelastin treatment only inhibits VSMC migration but leads to increased inflammatory response in EC. However, combined treatment with fibronectin, fibrinogen and tropoelastin inhibits VSMCs while reducing the inflammatory effects on EC (17). Therefore, coating a mixture of fibronectin/fibrinogen/tropoelastin on a stent may promote re-endothelialization and induce a better vascular repair following vascular intervention.…”
mentioning
confidence: 99%